Detection of Induction Drive Fault Based on Identification Model - Janickas, R.; Savickiene, Z. (Elektronika ir Elektrotechnika, 2014)
Parameters of induction motor due to nonlinearity of magnetic circuit causes difficulties in their identification, therefore difference in experimental and simulation results is observed. In this study, demand of motor diagnostic is described, fault costs are analysed. Adaptive simulation model including comparison of simulated and experimental results is developed and presented. DOI: http://dx.doi.org/10.5755/j01.eee.20.4.6885